Síntese e caracterização de perovskitas do tipo La (FexV1-x) 03 - Tupan, Lilian Felipe da Silva (2014)
Perovskites of the La(FexV1-x)O3 type were synthesized by solid state reaction and by arc-melting. The samples prepared were structurally characterized by X-ray diffraction and regarding the magnetic and hyperfine properties by 57Fe Mössbauer spectroscopy. The results revealed hat the samples crystallized mostly with orthorhombic structure, in the Pbnm space group. The lattice parameters of the pseudo-ternary compounds decreased linearly with the progressive substitution of iron by vanadium, in agreement with the Vegard's law. It was also observed the reduction of the hyperfine magnetic field which changes from a well defined sextet of 51,8 T, obtained for LaFeO3, to a magnetic field distribution and, further, to a paramagnetic component for the richest vanadium samples. Low temperature Mössbauer spectroscopy measurements were additionally performed for the La(Fe0,2V0,8)O3 sample It was shown that the sample recovers the magnetic order with decreasing temperature. These results reveal that the coexistence of iron-vanadium results in an even more complicated magnetic behavior, decreasing the magnetic transition temperature, as replacement of iron by vanadium in orthoferrite increases.